Development and Functions of the Infant Gut Microflora: Western vs. Indian Infants - Lalit Bharadia; Neha Agrawal; Nandan Joshi (International Journal of Pediatrics)
The human gut is colonized by trillions of bacteria as well as other microorganisms, collectively referred to as the “gut microflora.” This microflora plays an important role in metabolism as well as immunity, and alterations in its normal composition and pattern of colonization can disturb the development and functioning of the immune system, predisposing the individual to several diseases. Neonates acquire their gut microflora from the mother as well as the surroundings, and as the infant grows, the gut microflora undergoes several changes, ultimately acquiring an adult-like composition. Characterization of the gut microflora of healthy infants is important to protect infants from infectious diseases. Furthermore, formulation of prebiotics and probiotics for boosting infant immunity in a specific population also requires prior knowledge of the normal gut microflora in a healthy infant in that population. To this end, several studies have been performed on Western infants; however, the gut microflora of Indian infants is as yet insufficiently studied. Moreover, there has been no comparative analysis of the development and characteristics of the infant gut microflora between the two populations. In this review, we discuss the development and maturation of the infant gut microflora and its effect on immunity, as well as the factors affecting the patterns of colonization. In addition, we compare the patterns of colonization of gut microflora between Western and Indian infants based on the available literature in an attempt to identify the extent of similarity or difference between the two populations.